Subthalamic nucleus deep brain stimulation on motor-symptoms of Parkinson's disease: Focus on neurochemistry. (April 2017) - Stefani, A.; Trendafilov, V.; Liguori, C.; Fedele, E.; Galati, S.
Highlights: Chapter 1: focus on the complex interplay between subthalamic nucleus (STN)—deep brain stimulation (DBS) and levodopa (LD)-based therapy. Does stereotactic neurosurgery act in synergy with dopaminergic drug treatments?. Chapters 2 and 3: impact of STN-DBS on endogenous transmitters on basal ganglia (BG) including catecholamine, endogenous amino acids, and endogenous nucleotides. Chapter 4: effect of STN-DBS on cortical plasticity. Abstract: Deep brain stimulation (DBS) has become a standard therapy for Parkinson's disease (PD) and it is also currently under investigation for other neurological and psychiatric disorders. Although many scientific, clinical and ethical issues are still unresolved, DBS delivered into the subthalamic nucleus (STN) has improved the quality of life of several thousands of patients. The mechanisms underlying STN-DBS have been debated extensively in several reviews; less investigated are the biochemical consequences, which are still under scrutiny. Crucial and only partially understood, for instance, are the complex interplays occurring between STN-DBS and levodopa (LD)-centred therapy in the post-surgery follow-up. The main goal of this review is to address the question of whether an improved motor control, based on STN-DBS therapy, is also achieved through the additional modulation of other neurotransmitters, such as noradrenaline (NA) and serotonin (5-HT). A critical issue is to understand not only acute DBS-mediated effects, but also chronic changes, such as those involving cyclic nucleotides, capable of modulating circuit plasticity. The present article will discuss the neurochemical changes promoted by STN-DBS and will document the main results obtained in microdialysis studies. Furthermore, we will also examine the preliminary achievements of voltammetry applied to humans, and discuss new hypothetical investigational routes, taking into account novel players such as glia, or subcortical regions such as the pedunculopontine (PPN) area. Our further understanding of specific changes in brain chemistry promoted by STN-DBS would further disseminate its utilisation, at any stage of disease, avoiding an irreversible lesioning approach.